Uniqueness and Generalization in Organizational Psychology: Research as a Relational Practice - Scaratti, Giuseppe; Ivaldi, Silvia (Frontiers in Psychology, 2021)
The paper addresses the epistemological and theoretical assumptions that underpin the concept of Work and Organizational Psychology as idiographic, situated and transformative social science. Positioning the connection between uniqueness and generalization inside the debate around organization studies as applied approaches, the contribution highlights the ontological, gnoseological and methodological implications at stake. The use of practical instead of scientific rationality is explored, through the perspective of a hermeneutic lens, underlining the main features connected to the adoption of an epistemology of practice. Secifically the contribution depicts the configuration of the applied research as relational practice, embedded in the unfolding process of generating knowledge dealing with concrete social contexts and particular social objects. The discussion of a case study regarding an on the field research, allows to point out challenges and constraints connected to the enactment of the research process as a social accomplishment.